III-nitride-based optochemical transducers for gas detection - Maier, Konrad; Justus Liebig University Giessen (My University, 2018)
Customers of modern airplanes not only demand that manufacturers address more efficient propulsion systems but also pollution created by the overall aircraft system. One way of decreasing pollution is the replacement of kerosene burning auxiliary power units (APU) with hydrogen fuel cells. The usage of fuel cells requires a gas sensor system for safe application in an aircraft, and this can be achieved using a novel gas sensitive InGaN/GaN nanowire arrays (NWA) with an optical read out. These NWAs are investigated in this thesis and exhibit an efficient photolumines-cence (PL) which extends to temperatures of 200°C and beyond and show a chemical sensitivity towards gases and liquids. The gas sensing test revealed that InGaN/GaN NWA can have a quenching or an enhancing PL when exposed to different gas atmos-pheres which depends on both the type of adsorbate and the operation conditions of the transducer. All groups of tested analytes have in common that they can be described using a Langmuir adsorption isotherm. However, the adsorption energy and the response direction is gas species dependent. Oxidizing gases such as O2, NO2 and O3 quench the PL intensity whereas hydrocarbons, under the certain conditions, can increase the PL. Evaluation of the Langmuir adsorption energy showed an approximately linear increase with temperature in the range from room temperature to 150°C. This phenomenon was attributed to a competitive adsorption process onto a limited number of adsorption sites on the InGaN/GaN surfaces. Hydrocarbons showed an insignificant gas response when these are diluted in nitrogen. However, a PL enhancing effect can be observed when these gases are diluted in synthetic air and this effect is increased at elevated temperatures. This behavior is attributed to an indirect gas sensing process which includes a surface oxidation reaction of the analytes and a removal of PL quenching pre-adsorbed oxygen and formation of combustion products such as CO2 and H2O. CO2 hardly shows any effect on the PL intensity but H2O shows an interesting effect on the PL intensity as it can be of PL quenching and PL enhancing nature depending on the operation conditions. In the low temperature and excitation energy regime water molecules are able to increase the surface recombination process but at elevated temperatures and due to electrochemically dissociated water molecules these recombination channels are passivated and the PL is enhanced.

Auf den Anforderungslisten für moderne Flugzeuge stehen nicht nur effiziente An- triebssysteme, sondern ein möglichst ökologisches Gesamtflugzeugsystem. Eine Möglichkeit, die Umweltverschmutzung zu verringern, ist der Ersatz von kerosinbetriebenen Hilfsaggregaten (APU) durch Wasserstoff-Brennstoffzellen. Der Einsatz von Brennstoffzellen erfordert ein Gassensorsystem für den sicheren Betrieb in einem Flugzeug, was mit einem neuartigen gasempfindlichen InGaN/GaN-Nanodraht-Array (NWA) mit optischer Auslesung erreicht werden kann. Solche NWA, dessen Photolumineszenz (PL) auch bei Temperaturen über 200°C stabil ist und eine Sensitivität gegenüber Gasen und Flüssigkeiten aufweist, wurden im Rahmen dieser Arbeit untersucht. Gassensor-Tests ergaben, dass die PL des InGaN/GaN NWA sowohl verstärkt als auch reduziert werden kann wenn es unterschiedlichen Gasatmosphären ausgesetzt wird, was sowohl von der Art des Adsorbats als auch von den Betriebsbedingungen des Transducers abhängt. Bei allen untersuchten Gasen konnten Langmuir-Adsorptionsisothermen deren Adsorption beschreiben. Die Adsorptionsenergie und die Richtung des Gasresponses sind jedoch von der Art des Gases abhängig. Oxidierende Gase wie O2, NO2 und O3 reduzieren die PL-Intensität, während Kohlenwasserstoffe unter bestimmten Bedingungen die PL erhöhen können. Die Auswertung der Langmuir-Adsorptionsenergie ergab einen annähernd linearen Anstieg im Bereich von Raumtemperatur bis 150°C. Dieses Phänomen wurde auf einen konkurrierenden Adsorptionsprozess auf der InGaN/GaN-Oberfläche zurückgeführt. Kohlenwasserstoffe zeigten eine unwesentliche Gasreaktion wenn diese in Stickstoffhintergrund gemessen wurden. Ein PL-verstärkender Effekt kann jedoch beobachtet werden, wenn diese Gase in synthetischer Luft gemischt werden und dieser Effekt wurde bei erhöhten Temperaturen noch weiter verstärkt. Dieses Verhalten wird einem indirekten Gasdetektionsprozess zugeschrieben, der eine Oberflächenoxidationsreaktion der Analyten mit einer Verdrängung von adsorbiertem Sauerstoff und der Bildung von Verbrennungsprodukten wie CO2 und H2O beinhaltet. CO2 hat kaum einen Einfluss auf die PL, aber H2O zeigt einen interessanten Einfluss auf die PL-Intensität, da es je nach Betriebsbedingungen der NWA von PL-reduzierender als auch PL-verstärkender Natur sein kann. Im Niedrigtemperatur- und Anregungsenergiebereich sind Wassermoleküle in der Lage, den Oberflächenrekombinationsprozess zu verstärken, aber bei erhöhten Temperaturen und durch elektrochemisch-dissoziierte Wassermoleküle werden diese Rekombinationskanäle passiviert und die PL erhöht.
Keywords: III-nitride semiconductors; nanowires; photoluminescence; gas sensors; chemical sensors; ddc:530